‘사건’개념을 적용한 중국 사천남부 전통주택(川南民居)의 스토리텔링에 관한 연구 - 오소룡(Oh Soryong); 이민(Lee Min) (인문사회과학연구, 2024)
· 연구 주제: 본 연구는 '사건'의 개념을 중국 남사천 전통건축의 스토리텔링 특성에 적용하여 지역의 역사문화적 정체성을 깊이 있게 조명한다. 자공옌 상인의 저택 후선이탕, 쓰촨 뤄지아타운 댜오루민가옥, 징옌현 흥커우의 전거 등의 사례 분석을 통해 사건 개념과 잠재성, 특수성, 계열성, 우연성의 건축적 요소들 간의 상호작용을 탐구했다. · 연구 배경: 사천 남부 지역의 독특한 민가 건축은 자연, 문화, 심미적 관점을 반영하며, 중국 민가 건축 중 가치 있는 문화유산으로 자리잡고 있다. '사건' 개념을 적용한 스토리텔링 연구는 사천 남부 민가의 건축적 특성과 역사적 맥락을 조명하고, 이를 통해 공간의 의미와 삶의 방식을 탐구한다. 이 접근은 관람객들에게 사천 남부 민가와 그들의 삶의 이야기를 교육적이고 감성적으로 전달하여 의미있는 정보를 제공할 수 있다. · 선행연구와의 차이점: 본 논문은 사천 남부 민가의 역사와 문화, 건축 양식을 연구함으로써 지역적 특색과 전통을 보존하고 전승하는 데 중요한 가치를 파악하였다. 또한, 본 연구는 사천 남부 지역의 민가 건축이 어떻게 현대적 맥락에서 재해석되고 재발견될 수 있는지를 탐색함으로써, 이 지역의 독특한 문화유산을 강조하고 보존하는 데 기여하였다. · 연구방법: 본 연구는 사천 남부 지역의 전통 건축과 문화를 심층적으로 이해하기 위해 다각적인 방법을 사용한다. 먼저, 문헌 연구를 통해 역사적 자료와 학술 논문을 분석하여 이론적 기반을 마련하고, 자공시와 루저우의 전통 주택 건축의 역사적, 문화적 배경을 탐구한다. 핵심 요소인 현장 조사에서는 자공시와 루저우의 전통 건축물을 직접 방문하여 건축적 특성과 문화적 가치를 분석하고, 현지 주민들과의 인터뷰를 통해 현대 사회에서의 인식과 사용에 대한 유용한 정보를 도출하였다. · 연구결과: 본 연구에서 분석을 통해 드러난 잠재적 서사는 건축물이 단순한 공간을 넘어서 역사와 문화의 증거로 기능한다는 점을 강조한다. 상이적 서사는 각 건축물이 가지는 독특한 이야기와 그것이 지역 사회와 어떻게 상호 작용하는지를 탐구하며, 동일적 서사는 이 지역의 전통 건축이 공통적으로 가족 중심의 사회 구조와 긴밀한 공동체 의식을 반영하는 방식을 보여준다. 유동적 서사는 전통 건축이 시간과 공간에 따라 어떻게 변화하고 적응해왔는지를 탐구하며, 건축물이 고정된 구조가 아닌 변화하는 요구와 역사적 사건에 반응하여 발전하는 살아 있는 유산임을 강조한다. · 공헌점 및 기대효과: 본 연구는 사천 남부 지역의 전통 건축 및 문화 연구에 기여하며, 건축물 보존 및 복원 작업에 실질적인 지침을 제공할 것이다. 스토리텔링을 통해 건축물의 잠재적 의미를 전달하여 이 지역의 독특한 건축 유산을 보존하고 전승하는 데 기여하고, 사천 남부 민가의 역사와 문화, 건축 양식을 통해 지역적 특색과 전통을 유지하는 데 중요한 역할을 할 것으로 기대된다. · Research topics: This study deeply illuminates the historical and cultural identity of the region by applying the concept of 'event' to the storytelling characteristics of traditional architecture in Namsacheon, China. The interaction between the concept of events and the architectural elements of potential, specificity, sequence, and contingency was explored through case analysis such as Hsu Shen Yi-tang, the mansion of a merchant of Jiaxuan, Diaolumin House in Luogia Town, Sichuan, and the residence of Heungkou, Jingyan County. · Research background: The unique private house architecture in the southern part of Sacheon reflects the natural, cultural, and aesthetic perspectives and is positioned as a valuable cultural heritage among Chinese private house architecture. The storytelling study applies the concept of 'event' to illuminate the architectural characteristics and historical context of private houses in southern Sacheon and explores the meaning of space and way of life through it. This approach can provide meaningful information by conveying the stories of private houses in southern Sacheon and their lives to visitors educationally and emotionally. · Differences from prior research: This paper identified important values in preserving and transmitting regional characteristics and traditions by studying the history, culture, and architectural style of private houses in southern Sacheon. In addition, this study contributed to the emphasis and preservation of the unique cultural heritage of the area by exploring how the architecture of private houses in southern Sacheon can be reinterpreted and rediscovered in a modern context. · Research method: This study uses a multifaceted method to deeply understand the traditional architecture and culture of the southern part of Sacheon. First, through literature research, historical data, and academic papers are analyzed to establish a theoretical basis, and the historical and cultural background of the traditional housing architecture of Jagosong and Luzhou is explored. In the field survey, which is a key element, the traditional buildings of Jagosong and Luzhou were directly visited to analyze architectural characteristics and cultural values, and useful information on perception and use in modern society was derived through interviews with local residents. · Research results: The potential narrative revealed through analysis in this study emphasizes that buildings function as evidence of history and culture beyond simple spaces. The different narrative explores the unique story of each building and how it interacts with the community, and the same narrative shows how traditional architecture in the area reflects a family-centered social structure and a close sense of community in common. The fluid narrative explores how traditional architecture has changed and adapted over time and space and emphasizes that buildings are living heritage that develops in response to changing demands and historical events rather than fixed structures. · Contribution points and expected effects: This study will contribute to the study of traditional architecture and culture in the southern part of Sacheon and provide practical guidelines for the preservation and restoration of buildings. It is expected that it will contribute to the preservation and transmission of the unique architectural heritage of the area by conveying the potential meaning of the building through storytelling and play an important role in maintaining regional characteristics and traditions through the history, culture, and architectural style of the southern part of Sacheon. KCI Citation Count: 0